Linguagem e significado nas investigações filosóficas de Wittgenstein: uma análise do argumento da linguagem privada - Donat, Mirian (Universidade Federal de São Carlos, 2008)
This thesis analyzes the idea of meaning as language use, developed by Wittgenstein in the Philosophical Investigations, with the specific purpose of understanding the role played by the so-called private language argument in the elaboration of this concept. The concept of meaning as language use, which is based on the language games concepts, forms of life, family resemblance and the rules-following, is presented by Wittgenstein as an alternative to the concepts of meaning that were based on subjective and private experiences, that Wittgenstein considered as one of the images that has caused the greatest misunderstandings for the correct understanding of the language functioning. According to Wittgenstein, the acceptance of this image leads to skepticism concerning meaning, for if we have to accept that the basis of meaning is the subjective experience, we also have to accept that the association between word and experience takes place privately as well as accept the existence of subjective criteria of discrimination and identification of experiences, consequently subjective criteria for the correction or not of the use of the corresponding words. Now, according to Wittgenstein, a subjective criterion is not in fact a criterion and, opposing to this notion, he states that language has always a common origin and use and that, because of this, meaning always depends on this common use of words that happens in language games that, in turn, are developed in opposition to the forms of life background. The private language argument plays an important role for the elaboration of the concept of meaning as use, because with this argument Wittgenstein intends to demonstrate that, even for subjective experiences, for that which seems absolutely private, it is necessary to have public criteria of discrimination and identification.
Keywords: Linguagem; Significado; Wittgenstein, Ludwig Josef Johann, 1889-1951; CIENCIAS HUMANAS::FILOSOFIA